Tour Operator Love Voyage El Salvador - Hernandez Escobar, Noe Santiago
In this work you can find very important information about tourism and how it has impacted the economy, not only a brief look at the history of tourism in general, but also how tourism began in El Salvador. The profile of a tourist service called tour operator “Love Voyage EL Salvador” presented by three young people from the National University of El Salvador. The importance of natural resources and their sustainability, how to help the environment by making responsible use by learning to take care of it, you will be able to find important information about Salvadoran culture such as its festivals, festivals and legends and stories that are part of the cultural wealth of EL Salvador, the most recognized typical dishes of Salvadoran gastronomy. If you are an entrepreneur or would like to know more about it, you can find information about the profile of an entrepreneur, its responsibilities and its characteristics that can lead you to be a great entrepreneur and overcome all the obstacles that it presents in the course of development. How to identify your market niche, what characteristics it should have and how to know what your market niche is and take advantage of its elements to develop your business. In the end you will be able to find cost plan for the tourist product or service of the tour operator Love voyage El Salvador, the characteristics such as its logo, slogan, mission, vision, etc.